ANATOMICAL CHARACTERISTICS AND CHEMICAL PROPERTIES OF THE BRANCH-WOOD OF Schizolobium amazonicum DUCKE SPECIES AND ITS POTENTIAL USES - Amin, Yusup; Adi, Danang S.; Wahyuni, Ika; Kusumah, Sukma S.; Damayanti, Ratih (Indonesian Journal of Forestry Research, 2013)
The scale of forest degradation and deforestation in Indonesia has inspired the use of lesser-known wood species, which are potentially abundant and so far has not much been utilized. Utilization of these woods should be imposed not only of the stem wood but also of the branch-wood portions. Schizolobiumamazonicum Ducke treeis one of those lesser-known species, and growing fast with an MAIof3.68 cm/year.In Indonesia this species is only found in the Purwodadi Botanical Garden. A research was conducted to study the basic characteristics (anatomical aspects and chemical properties) of the branch-wood portion of this species. The branch-wood materials were obtained from the Purwodadi Botanical Garden situated in Pasuruan (East Java). The specimens used were the first branch of the trunk (stem) of nine-year old S. amazonicum tree (= 29.46 cm). The branch-wood samples were then examined for the anatomical aspects (macroscopic and microscopic characteristics) and chemical properties (chemical composition). Results revealed that the anatomical properties of S.amazonicum branch-wood exhibited close similarities to those of sengon wood; it was light in appearance and white in color. Its fiber averaged about 1500 Î¼m, and based on the fiber dimensions derived values the branch- wood fiber of this species was categorized into first-class quality for pulp and paper manufacture. Further, the chemical composition of this branch-wood compared favorably with that of sengon and mangium wood. The composition of extractive content thatsoluble in alcohol-benzene; lignin; holocellulose; and Î±-cellulose of this branch-wood were 2.46; 28.71; 80.64; and 50.47%, respectively. The overall assessment implied that the branch-wood portion of S.amazonicum tree affords favorable potential to be developed as raw material for pulp and paper manufacture. Also, considering that both sengon and mangium woods were already used in the pulp and paper industries as well as the trees are used for the establishment of industrial plantation forests (HTI), therefore S.amazonicum trees, as fast- growing species,are also promising for the establishment of pulp/paper-HTI for their branch-wood.